2018
DOI: 10.1111/imj.13742
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of patients with severe and severe‐complicated Clostridium difficile infection treated with tigecycline combination therapy: a retrospective observational study

Abstract: Tigecycline appears safe and effective as a part of combination therapy in severe CDI, and may be given earlier and for shorter durations than in current guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…69 A small observational study found intravenous tigecycline (loading dose of 100 mg followed by 50 mg BID) as adjunct therapy to be marginally favorable to metronidazole-vancomycin therapy in terms of mortality. 70 Tigecycline monotherapy was superior in terms of progression to complicated disease and clinical cure when compared with combination therapy in a retrospective study with 90 patients. 71 A matched study did not find a difference in cure or recurrence when tigecycline was added to vancomycin therapy 72 ; another study found no mortality benefit when it was added to standard of care in a patient cohort primarily comprising of severe-complicated CDI.…”
Section: Treating Severe and Severe-complicated (Fulminant) Diseasementioning
confidence: 97%
“…69 A small observational study found intravenous tigecycline (loading dose of 100 mg followed by 50 mg BID) as adjunct therapy to be marginally favorable to metronidazole-vancomycin therapy in terms of mortality. 70 Tigecycline monotherapy was superior in terms of progression to complicated disease and clinical cure when compared with combination therapy in a retrospective study with 90 patients. 71 A matched study did not find a difference in cure or recurrence when tigecycline was added to vancomycin therapy 72 ; another study found no mortality benefit when it was added to standard of care in a patient cohort primarily comprising of severe-complicated CDI.…”
Section: Treating Severe and Severe-complicated (Fulminant) Diseasementioning
confidence: 97%
“…These data support the use of tigecycline in complicated and severe C difficile infection. Two retrospective studies confirm the safety of the drug in severely infected patients118 but failed to show an improvement compared with standard therapy in clinical cure or recurrence rate 119. If tigecycline is used to treat severe infections, it should be considered a substitute to metronidazole as adjunctive therapy to vancomycin.…”
Section: Treatmentmentioning
confidence: 99%
“…84 Recently published retrospective studies have shown conflicting results regarding the efficacy of tigecycline for fulminant CDI. 85,86,87,88 Because of the poor outcomes associated with fulminant CDI, there may be a role for adjunctive tigecycline. 84 Consideration of surgical intervention and faecal microbiota transplantation (FMT) in such settings is also indicated.…”
Section: What Are the Recommended Treatment Options For An Initial Episode Of Fulminant Clostridioides Difficile Infection?mentioning
confidence: 99%